The Relationship Between Maternal Employment, Social Spending and Child Obesity Prevalence: An Analysis of OECD Countries (Third Sector Social Economic Review, 2026)
This study investigates the effect of maternal employment on obesity prevalence among children aged 5-9, and the moderating role of social spending on families in this relationship, using panel data for 25 OECD countries spanning the period 2006-2021 and employing fixed-effects model. First, the relationship between maternal employment and child obesity prevelance is analysed using a fixed-effects model that incorporates the control variables (women’s tertiary education rate, urbanization, youth dependency ratio, mothers’s average age at childbirth, GDP per capita, and family oriented social spending). The findings indicate that maternal employment alone does not have a significant effect on obesity prevelance for either girls or boys. Subsequently, an interaction term between maternal employment and family-oriented social ependitures is added to the model, and analysis is repeated. The interaction term is found to be statistically significant and negative for both genders. This key finding reveals that both the direction and the magnitıtude of the effect of maternal employment are sensitive to the level of public spending on families. In other words, within the sample of 25 countries, social spending appear to moderate the effect of maternal employment on child obesity in a mitigating direction. The results are supported by marginal effect analysis and margin plots. For girls, the obesity reducing effect of maternal employment becomes stronger as social spending increases. This effect is clear and statistically significant. Although higher level of social spending also lead maternal employment to have an obesity-reducing effect for boys, this effect is weaker and statistically less significant compared to girls. The study is significant in demonstrating that the relationship between maternal employment and child obesity should not be evaluated in a one-dimentional manner, as social policy instruments play a crucial role in shaping this relationship. Ultimately, investments in childcare, parental leave policies and family-friendly labour market regulations may have a protective mechanisms against childhood obesity.
Keywords: Maternal Employment; Chilhood Obesity; OECD Countries; Panel Data Analysis; Social Spending